Joint inversion of gravity and surface wave data constrained by magnetotelluric: Application to deep geothermal exploration of crustal fault zone in felsic basement. (July 2019) - Ars, Jean-Michel; Tarits, Pascal; Hautot, Sophie; Bellanger, Mathieu; Coutant, Olivier; Maia, Marcia
Highlights: Geophysical joint inversion highlight unconventional geothermal prospect. Inversion non-uniqueness reduced by the joint inversion approach. Linear coupling between model parameters enforce relationship in geological domain. Abstract: Geophysical exploration in unconventional geothermal reservoir is challenging because of the lack of structures with specific geophysical signature such as a clay cap above volcanic geothermal reservoirs. The combination of several geophysical methods such as magnetotelluric (MT), gravity and seismic methods provides complementary insight into the geothermal reservoir. We present a joint inversion approach of ambient noise surface wave and gravity constrained by the 3D distribution of electrical resistivity. The method is applied to analyze the potential of unconventional deep geothermal resources in the French Massif Central (FMC). We coupled the resistivity, density and shear wave velocity with a linear correlation. We characterized the common properties in relation to the geological domains down to about 10–15 km. We validated the proposed approach on a synthetic model derived from models obtained from each independent geophysical method. The joint inversion limited the non-uniqueness of the gravity and the ambient noise tomography inversion and allow to recover the features of the synthetic models. We applied the method to real field data acquired in the Sioule Valley, Massif Central, France. The joint features observed in the geophysical models suggest a deep heat source associated with a possible shallow (∼6–8 km) brittle–ductile transition. A large fault zone, the Pongibaud Fault zone, seems to become listric and connect the surface to this transition zone to possibly constitute a permeable path for water circulation.